2021
DOI: 10.3390/land10050520
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Effect of Urban Agglomeration’s Transportation Network: Evidence from Chengdu–Chongqing Urban Agglomeration, China

Abstract: Recent years have seen the global proliferation and integration of transportation systems in urban agglomeration (UA), suggesting that transportation networks have become more prominent in the sustainable development of UA. Core cities play a radiating and driving role in affecting their adjacent cities to formulate transportation networks. Such a phenomenon is called the radiation effect of transportation networks and can be imaged using a field strength model as proposed in the study. The field strength mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 66 publications
(114 reference statements)
0
9
0
Order By: Relevance
“…Using word frequency screening, interviews, expert consultation, clustering techniques, and other methods, this study further screened the residential elements that impact the life of multi-child families in order to thoroughly analyze the root problems encountered by multi-child families (Figure 2). To start with, this study draws on the consensus reached by Changlian Zhu, Hao Long [40], Renlu Hu, Zhou Yanmin [41], Fang Xianfu, and Yao Shizhang [42] as the basic framework. Next, the study conducted online interviews with 95 multi-child families for the purpose of its preliminary research, identified the factors influencing their housing, and conducted the first round of expert consultation (15 experts) to summarize their characteristics, categorizing residential elements into three major categories: flat layout, flat public areas, and residential areas.…”
Section: Sample and Evaluation Frameworkmentioning
confidence: 99%
“…Using word frequency screening, interviews, expert consultation, clustering techniques, and other methods, this study further screened the residential elements that impact the life of multi-child families in order to thoroughly analyze the root problems encountered by multi-child families (Figure 2). To start with, this study draws on the consensus reached by Changlian Zhu, Hao Long [40], Renlu Hu, Zhou Yanmin [41], Fang Xianfu, and Yao Shizhang [42] as the basic framework. Next, the study conducted online interviews with 95 multi-child families for the purpose of its preliminary research, identified the factors influencing their housing, and conducted the first round of expert consultation (15 experts) to summarize their characteristics, categorizing residential elements into three major categories: flat layout, flat public areas, and residential areas.…”
Section: Sample and Evaluation Frameworkmentioning
confidence: 99%
“…From 1950 to the present, theories on the interaction between urban roads and urban society and other elements mainly focused on the biological environment and landscape [1][2][3][4][5][6], urban agglomeration and urbanization [7][8][9][10][11][12], industrial transformation [13][14][15][16], land agglomeration use [17][18][19][20][21], real estate development [22][23][24][25][26][27][28], location [29][30][31][32][33][34][35][36][37], mixed land use [38][39][40][41], and property right [42,43]. Based on quantitative models, scholars have conducted a lot of research mainly on the interaction between economy, social demand [44,45], land and transportation [46].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The network layout of transportation land leads to a more rapid circulation of passenger flow, logistics, capital flow, information flow, and other resources and services in the network within and between cities. This is due to the powerful aggregation and release effect, which changes modes of consumption, life, and production and has thereby profoundly affected the economic operation of the city [39,40].…”
Section: Time-space Lag Conduction Effect Of Tltmentioning
confidence: 99%